Interfacial free energies, nucleation, and precipitate morphologies in Ni-Al-Cr alloys: Calculations and atom-probe tomographic experiments. (March 2019) - Mao, Zugang; Booth-Morrison, Christopher; Sudbrack, Chantal K.; Noebe, Ronald D.; Seidman, David N.
Abstract: The effects of Cr additions on the morphologies οf γ′(L12 ordered) precipitates are studied in three Ni-Al-Cr alloys utilizing atom-probe tomography (APT) and first-principles calculations. We find that Cr and Al share the same sublattice sites in the L12 -structure: Chromium partitions from the L12 structure into the disordered f.c.c. matrix for a driving force of 0.436 eV atom −1 . Mixing between the Ni3 Al(L12 ) and Ni3 Cr(L12 ) structures is energetically unfavorable based on first-principles quasi-random structure calculations. Interfacial Gibbs free energies of Ni/Ni3 Al(L12 ), Ni/Ni3 Cr(L12 ), Ni/Ni3 Cr(DO22 ), and Nin (Aly Cr1-y )/Ni3 (Alx Cr1-x )(L12 ) interfaces are calculated for the {100}, {110}, and {111} planes. The temperature dependencies of the interfacial Gibbs free energies are determined by including phonon vibrational entropies. The equilibrium interfacial Gibbs free energies are determined using concentration profiles as a function of aging time, obtained using APT. At early aging times, the initial values of the interfacial Gibbs free energies are higher with small Cr concentrations in the γ' (L12 )-precipitates. With increasing aging time, the interfacial Gibbs free energies decrease with increasing Cr concentration and achieve equilibrium values after 16-h of aging at 873 K (600 °C) for the three Ni-Al-Cr alloys. From classical nucleation theory, the nucleation of metastable Ni3 Cr(L12 ) is easier than Ni3 Al(L12 ) at 873 K (600 °C). Ni3 Cr(DO22 ) is more difficult to nucleate than Ni3 Cr(L12 ) and Ni3 Al(L12 ) at 873 K (600 °C). The Cr additions to Ni-Al alloys have significant effects on the critical radius and critical net reversible work of nucleation. With increasing Cr concentration, Ni3 (Al, Cr)(L12 ) requires the smallest critical net reversible work to form but has a larger critical size. An embryo of Ni3 Cr(L12 ) only acts as a nucleant for mixed L12 Ni3 (Alx Cr1-x ). The morphology of Ni3 (Al, Cr)(L12 ) precipitates transforms from cuboidal-to-spheroidal with increasing Cr concentration, in agreement with APT observations. Graphical abstract: The effects of Cr additions on the morphologies of γ′(L12 ordered) precipitates are studied in three Ni-Al-Cr alloys utilizing atom-probe tomography (APT) and first-principles calculations. The Cr additions to Ni-Al alloys have significant effects on the critical radius and critical net reversible work of nucleation. With increasing Cr concentration, Ni3 (Al, Cr)(L12 ) requires the smallest critical net reversible work to form but has a much larger critical size. An embryo of Ni3 Cr(L12 ) only acts as a nucleant for mixed L12 Ni3 (Alx Cr1-x ). The morphology of Ni3 (Al, Cr)(L12 ) precipitates transforms from cuboidal-to-spheroidal with increasing Cr concentration, in agreement with APT observations. Image 1